Effects of drying conditions on drying kinetics, product quality and retention of carpaine in papaya leaves (Carica papaya Linn.) - Yap, Jing Ying (2022)
Dengue fever causes mortality and morbidity worldwide which is a major concern to governments and the World Health Organization (WHO). It was reported that carpaine, the major active compound extracted from papaya leaves, contributes to the anti-thrombocytopenic activity. Hence, carpaine plays an important role in treating dengue patients by raising the platelet count in the patients’ blood. However, carpaine in papaya leaves could degrade easily when exposed to heat and sunlight during processing and storage. There is no literature reporting on the processing aspects (e.g., preparation, drying and storage) of papaya leaves and the leaves extract to date. This could possibly be due to papaya leaves have no commercial value and the leaves are usually treated as waste. Therefore, this thesis will focus on the effects of drying conditions on drying kinetics, product quality and retention of carpaine in papaya leaves.